Records of Parochlus steinenii in the Maritime Antarctic and sub-Antarctic regions - Ganan, Melisa; Contador Mejias, Tamara Andrea; Rendoll, Javier; Simoes, Felipe; Perez, Carolina; Graham, Gillian; Castillo, Simon; Kennedy, James; Convey, Peter (My University, 2021)
This study provides the summary of the reports of the geographical distribution in the Maritime Antarctic and sub-Antarctic regions of Parochlus steinenii (Gercke, 1889) (Diptera, Chironomidae), the only flying insect occurring naturally in the Antarctic continent. The distribution encompasses the South Shetland Islands (Maritime Antarctic), South Georgia (sub-Antarctic), and parts of the Cape Horn Biosphere Reserve (CHBR, southern Chile). In total 78 occurrence records were identified, 53 from our own records, 19 from the literature, and six from other data present in GBIF. Of the 78 records, 66 are from the South Shetland Islands, eight are from South Georgia, and four from the CHBR. This database was developed as one of the main objectives of two Chilean-funded research projects addressing understanding the effects of climate change on sub-Antarctic and Antarctic insects. It provides dataset documenting the distribution of Parochlus steinenii in the Maritime Antarctic, the sub-Antarctic, and the CHBR in southern South America (Chile). The complete dataset is available in Darwin Core Archive format via the Global Biodiversity Information Facility (GBIF).
Keywords: cape horn biosphere reserve; parochlus steinenii; south georgia; south shetland islands; winged antarctic midge